Knowledge management and connectivity: mainstay in turbulent times - Fonseca-Cifuentes, Gina P. (Unidad Editorial UPTC, 2020)
The profound global changes associated with the health, social and economic crisis, resulting from the new coronavirus COVID-19 (Du et al., 2020; Estalella, Zabalegui, and Guerra, 2020; Huang et al., 2020), have highlighted the barriers to innovation in healthcare systems, justified in weak knowledge and technological processes, uncertainty and people's rejection of modification in routine patterns, revealing in general terms aversion to change (García-Alegría and Gómez-Huelgas, 2020), however demonstrating the imperative need for a rapid response capacity in the face of these emerging or sudden changes, in a highly turbulent environment (Burnes, 2005; Sandoval Duque, 2014). Received: 10/06/2020.  Accepted: 15/06/2020.  Published: 18/06/2020.